Aromatic amino acid decarboxylase deficiency: Molecular and metabolic basis and therapeutic outlook - Himmelreich, Nastassja; Montioli, Riccardo; Bertoldi, Mariarita; Carducci, Carla; Leuzzi, Vincenzo; Gemperle, Corinne; Berner, Todd; Hyland, Keith; Thöny, Beat; Hoffmann, Georg F.; Voltattorni, Carla B.; Blau, Nenad (Molecular genetics and metabolism, 2019)
Aromatic-l-amino acid decarboxylase (AADC) deficiency is an ultra-rare inherited autosomal recessive disorder characterized by sharply reduced synthesis of dopamine as well as other neurotransmitters. Symptoms, including hypotonia and movement disorders (especially oculogyric crisis and dystonia) as well as autonomic dysfunction and behavioral disorders, vary extensively and typically emerge in the first months of life. However, diagnosis is difficult, requiring analysis of metabolites in cerebrospinal fluid, assessment of plasma AADC activity, and/or DNA sequence analysis, and is frequently delayed for years. New metabolomics techniques promise early diagnosis of AADC deficiency by detection of 3-O-methyl-dopa in serum or dried blood spots. A total of 82 dopa decarboxylase (DDC) variants in the DDC gene leading to AADC deficiency have been identified and catalogued for all known patients (n=123). Biochemical and bioinformatics studies provided insight into the impact of many variants. c.714+4A>T, p.S250F, p.R347Q, and p.G102S are the most frequent variants (cumulative allele frequency=57%), and c.[714+4A>T];[714+4A>T], p.[S250F];[S250F], and p.[G102S];[G102S] are the most frequent genotypes (cumulative genotype frequency=40%). Known or predicted molecular effect was defined for 79 variants. Most patients experience an unrelenting disease course with poor or no response to conventional medical treatments, including dopamine agonists, monoamine oxidase inhibitors, and pyridoxine derivatives. The advent of gene therapy represents a potentially promising new avenue for treatment of patients with AADC deficiency. Clinical studies based on the direct infusion of engineered adeno-associated virus type 2 vectors into the putamen have demonstrated acceptable safety and tolerability and encouraging improvement in motor milestones and cognitive symptoms. The success of gene therapy in AADC deficiency treatment will depend on timely diagnosis to facilitate treatment administration before the onset of neurologic damage.